T cells expressing CD19-specific Engager Molecules for the Immunotherapy of CD19-positive Malignancies - Velasquez, Mireya Paulina (Sci Rep, 2016)
T cells expressing chimeric antigen receptors (CARs) or the infusion of bispecific T-cell engagers (BITEs) have shown antitumor activity in humans for CD19-positive malignancies. While BITEs redirect the large reservoir of resident T cells to tumors, CAR T cells rely on significant in vivo expansion to exert antitumor activity. We have shown that it is feasible to modify T cells to secrete solid tumor antigen-specific BITEs, enabling T cells to redirect resident T cells to tumor cells. To adapt this approach to CD19-positive malignancies we now generated T cells expressing secretable, CD19-specific BITEs (CD19-ENG T cells). CD19-ENG T cells recognized tumor cells in an antigen-dependent manner as judged by cytokine production and tumor killing, and redirected bystander T cells to tumor cells. Infusion of CD19-ENG T cells resulted in regression of leukemia or lymphoma in xenograft models and a survival advantage in comparison to control mice. Genetically modified T cells expressing engager molecules may present a promising addition to current CD19-targeted immunotherapies.